ANALISIS KEMANDIRIAN ANAK USIA 5-6 TAHUN DI PAUD BHAKTI BUNDA KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Illahi, Sri Rahyu; ', H. Zulkifli N; ', Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: An Initial observation of the independence of children aged 5-6 years in Early Childhood Education Bhakti Bunda Payung Sekaki District of Pekanbaru City showed that: 1) There is still a child who asks accompanied in the classroom when learning and fun activities in class, 2) There is also a turn in the assignment of teachers to his parents when learning and playing in class, 3) There are still finding children who are still very dependent on parents is often he cried when left at school by his mother, 4) To get help from the people around him, children are often whiny, 5) Whine and often catapult protests when seeing things that are not in accordance with his wishes, 6) Kids always say can not and always ask for help in completing its tasks, 7) In the process of teaching and learning always ask the teacher to sit beside him, 8) never completing the assignment of teachers to good. This study aimed to analyze the independence of children aged 5-6 years in Early Childhood Education Bhakti Bunda Payung Sekaki District of Pekanbaru City. The sample used in this research were 26 children. The data collection techniques were used observation. Data were analyzed using a percentage formula by entering the number of scores achieved divided by the maximum score and then multiplied by 100%. The results of the four research aimed to analyze the independence of children aged 5-6 years in Early Childhood Education Bhakti Bunda Payung Sekaki District of Pekanbaru City. The sample used in the indicator independence of children aged 5-6 years in Early Childhood Education Bhakti Bunda Payung Sekaki District of Pekanbaru City are in the category of